Pengaruh Beberapa Jenis Aktivator terhadap Mutu Kompos Eceng Gondok (Eichhornia crassipes) - ADITYA, MADE PANDE; KARTINI, NI LUH; SONIARI, NI NENGAH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
The Effect of Several Types of Activators on Quality of Water Hyacinths Compost ( Eichhornia crassipes ) Water hyacinths is a type of floating aquatic plant that has a high growth speed so that this plant is considered a weed that can damage the aquatic environment, therefore one of them needs to be processed into compost. this is a role from the control water hyacinths. The purpose is research was to see the effect of the best media and activator on the quality of water hyacinths compost, and the percentage of decomposition of compost matter. This research was conducted in Megati Village of Tabanan, Bali from January to March 2020. This study used a randomized block design with a simple pattern with one factor, namely 9 treatments that were repeated 3 times for a total of 27 replications with the composition of 1 kg water hyacinth with a concentration of worm compost 100 g up to 800 g , 50cc and 100 cc moles of rice,  EM4 3 ml  and 9 ml. Based on the results of research, the media and decomposers significantly affected C-organic, total N, C / N ratio, moisture content, and pH. The highest percentage of decomposition (80%) was found in the composition of the media (1 kg water hyacinth + 800 g vermicompost + 9 ml EM4) and the percentage of decomposition (35%) in the control treatment.